Appreciating Cow–Calf Contact: Evaluating prospective consumer segments in Germany through cluster analysis of alternative calf-rearing systemsMendeley Data - Flora von Steimker; Sarah Kühl (Journal of Agriculture and Food Research, 2025)
Public concern about early cow-calf separation and individual calf housing is increasing. In response, alternative calf-rearing systems, such as cow–calf contact (CCC) systems, including foster cow and dam rearing, are discussed. Existing research shows that consumers generally prefer systems in which calves have contact with their mothers. However, foster cow rearing presents a practical and economically viable alternative. Nevertheless, studies on consumer perception of this system remain scarce.This study aims to assess consumer and public acceptance of five calf-rearing systems and to identify target groups for products from CCC systems to offset higher costs.In an online survey, 996 Germans evaluated individual, pair, and group housing, foster cow, and dam rearing using images and brief descriptions. Acceptance, measured by four items per system, showed a stepwise increase from individual (mean = 2.1–2.6), pair (2.4–2.9), group (2.8–3.0), to foster cow (3.4–3.9) and dam rearing (3.7–4.1).Both CCC systems were highly accepted, although dam rearing received significantly higher acceptance. A cluster analysis based on acceptance factors of each system identified five consumer segments, two of which emerged as promising target groups (38 % of the total sample). One segment showed high acceptance of dam rearing (16 %), while the other was also open to foster cow systems (23 %). In contrast, other segments were either highly critical of cattle farming (14 %), uninterested in animal welfare products (22 %), or might be inclined to choose competing products (27 %). The study suggests communication strategies to target key consumer segments for CCC-system products.